Environmental education with particular reference to management of municipal - Sabina Zalewska (Studia Ecologiae et Bioethicae)
In the pursuit of success, stuck in the shadow of reality, we often forget that every day we use goods of the environment which surrounds us. We do not realize that the behavior of particular people, their families, and social groups influence the elements of natural history. This article focuses on the adjustment of our lifestyle to the idea of balanced development. That is why environmental education, which supports understanding the correlation between man, his products, and the environment, should be offered to all people, in particular the youngest, who will be able to direct the patterns of pro-environmental behavior to the elderly people.